2021
DOI: 10.3390/coatings11020225
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Evaluation of Phytosynthesized Silver Nanoparticles on Lettuce

Abstract: The increasing metal release into the environment warrants investigating their impact on plants, which are cornerstones of ecosystems. Here, Lactuca sativa L. (lettuce) seedlings were exposed hydroponically to different concentrations of silver ions and nanoparticles (Ag NPs) for 25 days to evaluate their impact on plant growth. Seedlings taking Ag+ ions showed an increment of 18% in total phenolic content and 12% in total flavonoid content, whereas under Ag NPs, 7% free radical scavenging activity, 12% total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…The NPs are clearly spherical in shape, but the size of the particles is not uniform. The nanospheres are composed of interconnected three-dimensional Se networks in which the stable chain and ring structure results in the spherical shape of the nanospheres. , Besides, the lack of uniformity of Se-NPs may be due to the short-term thermodynamic interaction, as the resulting particles tend to be adhere to each other . After that, by measuring the diameter of 100 nm size of particles in different areas of the SEM image, the histogram of the diameter distribution was plotted as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…The NPs are clearly spherical in shape, but the size of the particles is not uniform. The nanospheres are composed of interconnected three-dimensional Se networks in which the stable chain and ring structure results in the spherical shape of the nanospheres. , Besides, the lack of uniformity of Se-NPs may be due to the short-term thermodynamic interaction, as the resulting particles tend to be adhere to each other . After that, by measuring the diameter of 100 nm size of particles in different areas of the SEM image, the histogram of the diameter distribution was plotted as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, root growth was more affected by AgNPs than shoot growth and root cells were highly plasmolyzed and degraded by higher concentrations of AgNPs. Hasan et al [ 22 ] found the same results where AgNPs caused cell death at 100 ppm of the concentration on the lettuce. The results also showed an increasing number of starch grains in the chloroplasts at the low concentration of AgNPs (20 mg/L) and decreased at higher concentrations.…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported that AgNPs cause ultrastructural malformation in the cells of different plants such as rice [15], barley [16], Brassica [17], tobacco [18][19][20], and Scots pine and oak [21]. Also, [22] reported obvious changes in the anatomy of the lettuce leaves in response to the Ag NPs compared to the control. Patlolla et al [25] demonstrated that AgNPs reduced mitotic cell division in root tip cells of broad bean and induced chromosomal aberrations and micronuclei production suggesting a disruption in cell cycle and mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…NPs can increase the survival of plants through many mechanisms such as improving the antioxidant defense system, increasing the absorption of water, nutrients, and phytohormones, among others [ 30 ]. Hasan et al [ 31 ] reported that Ag-NPs increased the chlorophyll content of lettuce leaves by stabilizing the photosynthetic function; this was due to the optimal penetration into the leaf tissue. Zhao et al, [ 32 ] reported that the application of CuO-NPs increased the content of photosynthetic pigments in cucumber leaves, which was reflected in increased photosynthesis.…”
Section: Discussionmentioning
confidence: 99%